Discovery of Innate Immune Response mRNAs That Are Impacted by Structure-Specific Oral Baker’s Yeast Beta Glucan Consumption - Brian K. McFarlin; John H. Curtis; Jakob L. Vingren; David W. Hill; Elizabeth A. Bridgeman (BioTech)
The study of nutritional compounds with the potential to train the innate immune response has implications for human health. The objective of the current study was to discover by what means 6 weeks of oral baker’s yeast beta glucan (BYBG) supplementation altered the mRNA expression of genes that reflect innate immune training in the absence of a physical stressor. Nineteen adults were randomly assigned to either a Wellmune® BYBG or Placebo for 6 weeks. BYBG uniquely altered the expression of 40 mRNAs associated with Dectin-1 and trained innate immunity, the innate immune response, the pathogen-associated (PAMP) and damage-associated molecular pattern (DAMP), and the inflammatory response. The observed changes were classified as immune training rather than immune priming due to the progressive increase in the expression of myeloid immune-associated mRNA. Combined with the findings of previous research, the findings of the present study support the claim that oral BYBG supplementation may be associated with trained innate immunity during resting homeostasis. Further, the key findings associated with BYBG may reflect improved responsiveness to future infection (exogenous) and/or sterile-inflammatory (endogenous) challenge.